Pseudocapacitive augmentation of palm kernel shell carbon for high density supercapacitive charge storage - Vijayan, Bincy Lathakumary (2021)
Allotropes and polymorphs of carbon are a universal choice to fabricate the electrodes of energy storage devices such as batteries and supercapacitors; however, most of these biomass-derived carbons have a large volume of passive voids which do not contribute to the final functionality of the devices or their surface structure could still be tailored for enhanced performance. Owing to their renewability, developments of activated carbons (ACs) from non-edible biomass is an active area of research. This doctoral research focuses on the functionalization of biomass activated carbon synthesized from palm kernel shell (PKS) with low quantities (10 wt.%) of metal oxides or metals for their application as an energy storage electrode either in a supercapacitor or in a battery – supercapacitor hybrid device. Achieving energy density (ES) similar to that of batteries with similar power density (PS) as that of supercapacitors has been the principal target in this research. Towards this primary objective, Mn2O3 and metallic Co are coated as a thin layer on PKSAC and MnCo2O4 and TiO2 ceramic nanostructures loaded into the voids of AC. The materials were characterized using X- ray diffraction, field emission scanning electron microscopy, energy dispersive X-ray spectrometry, X- ray photoelectron spectroscopy, transmission electron microscopy with selected area electron diffraction analyses and gas adsorption measurements. Electrochemical properties of AC, inorganic materials and carbon – inorganic materials composites were evaluated using cyclic voltammetry, galvanostatic charge-discharge cycling and electrochemical impedance spectroscopy in three electrode configuration tested in 1 M Na2SO4 and in 1 M LiPF6 dissolved in 1:1 (volume) mixture of ethylene carbonate and diethyl carbonate. The AC electrodes give a specific capacitance (CS) of 150 F g-1 with a cyclic stability of 97% after 5000 cycles in 1 M Na2SO4 neutral electrolyte (potential ~1 V). The CS increased to three-folds with a capacitance retention of >97% after 5000 cycles when the voids are coated or filled with the inorganic materials. The AC electrodes filled with MnCo2O4 nanoflowers offers one of the highest CS (510 F g-1) and potential window (~1.2 V) in neutral electrolytes. A symmetric supercapacitor developed using the optimum electrodes showed nearly four times higher energy density than the pure AC owing to the enhancements in voltage window and capacitance. Moreover, AC and carbon – inorganic materials composites are tested as the cathode materials of Lithium Ion Capacitor (LIC). LIC with 10 wt.% MC @AC shows larger voltage window (~2.5 V), superior capacitance (160 F g-1) and rate capability than the pure analogue. These results demonstrate that the current protocol allows fabrication of superior charge storing electrodes using renewable materials functionalized by minimum quantity of earthborn materials. Furthermore, battery – supercapacitor hybrid device is fabricated with MnCo2O4 nanoflowers as anode and carbon composite with MnCo2O4 as cathode electrode shows ES of ~153 W h kg-1 at a minimum PS of ~214 W kg-1. This research describes full scale approach for improving the performance of AC by modifying the surface properties for their enhanced electrochemical performance.